Medicine as a career choice: a cross-sectional study on undergraduate medical students at King Abdulaziz University - Ayuob, Nasra N.; Sindi, Abdulrahman Hilmi; ElDeek, Basem S. (International Journal of Research in Medical Sciences, 2016)
Background: During the last 15 years large number medical schools have been launched in Saudi Arabia in order to compensate for the shortage of Saudi physicians. Till now the reasons for choosing the medical profession by Saudi students were not thoroughly investigated. This study aimed to investigate the reasons for study medicine at King Abdulaziz University (KAU); and if there is any difference in these reasons between the junior and senior medical student. Factors helping in profession selection as well as the future specialty selection were also investigated. Methods: This comparative cross section study was conducted at KAU during the year 2014-2015 using a self-administered questionnaire distributed to all the 2nd and 6th year medical students. Results: Like to help patients, interest in medical field and being prestigious career were the commonest causes of choosing the medical profession among the 2nd year students and they were significantly rated higher ( 0.031, 0.001, 0.028) in 2nd year students compared to the 6th year. Getting a high GPA was rated significantly higher (p=0.01) by the 6th year students than the 2nd year students. Publications and internet sources was the significant (p=0.001) helpful factors rated by the 2nd year students. Surgery, Pediatric and Internal medicine were the commonest future specialties that had been chosen by both 2nd and 6th year students. Conclusions: Comprehensive and structured programs directed to the secondary school and preparatory university year students to guide them to the proper career with the highlight of Medicine as one of the profession strongly needed in Saudi Arabia.